Carbon nanomaterials in biomedicine and the environment - Mansūrov, Z. A. (Singapore : Jenny Stanford Publishing Pte. Ltd., 2020)
Carbon nanomaterials possess special physical and chemical properties. As adsorbents, they are widely used for the purification of water and other liquids, recovery of valuable substances from liquid and gaseous media, and oil refining and also in petrochemical, wine, oil and fat, and other industries. They can be used in medicine, both for the creation of hemosorption systems that are capable of performing specific purification of blood and other physiological fluids, including removal of various exo- and endotoxicants, and for the construction of highly effective adsorbed probiotics.The creation of nanostructured carbon-containing materials is one of many rapidly developing research fields and also the theme of this book. The book focuses on the recent developments in the synthesis of nanostructured carbon multifunctional sorbents and covers topics such as fusicoccin compounds as anticancer agents, entero- and vulnerosorption, and blood purification. It will be useful for scientists, chemical industry specialists, professors, and master's and PhD students of chemical, physical, and biological sciences.
OCLC-licensed vendor bibliographic record.
Keywords: Nanostructured materials; Nanostructured materials -- Environmental aspects; Carbon; Nanostructured materials industry; MEDICAL / Biotechnology; SCIENCE / Chemistry / General; SCIENCE / Biotechnology